Flood monitoring and warning system for embankment using IoT - Dutta, Aparup; Roy, Sanchoy; Ahmed, Hatif Asrar (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.